Bibliometric analysis of interventions with batterers in spain - Victoria A. Ferrer-Perez (Universidad de San Buenaventura, 2015)
This study analyse the evolution and characteristics of scientific production on intervention programmes with gender violence perpetrators performed in Spain. The standard bibliometric indicators were applied to 148 studies identified. The greatest productivity is focused between 2008 and 2010 and the largest number of records corresponds to articles in specialised scientific journals. As far as authorship is concerned, an analysis of the number of studies per person indicates that the results obtained are only initially consistent with Lotka’s Law, that is, there are a majority of not very productive authors and a minority who publish frequently, but the data do not fit this law. An analysis of collaboration between authors enables us to determine the existence of one “Social Circle” or “Invisible College”, at least. Most of the records analysed focus on the description of one or several intervention programmes with men who abuse their partner. Results show that there are progressively more evidence based studies on batterers and their treatment.